THE RELATIONS OF TOTAL TOURISTS VISIT ON OPERATIONAL COST AT STARS HOTEL IN BULELENG DISTRICT - Yuniarta, Gede Adi (Universitas Pendidikan Ganesha, 2017)
This study aims to determine the relation of the number of tourist visits to the opearsional costs at Sunari Hotel. The subject of this research is Sunari Hotel which is located at Dusun Banyualit, Kalibukbuk Village, precisely on Jalan Raya Lovina - Kalibukbuk Singaraja Bali, while the object of research is Relationship Number of Tourist Visits To Operational Costs at Hotel Sunari. Data collection techniques used in this study are interviews, documentation, and literature study. Analysis technique used is correlation coefficient analysis technique. The result of the research shows that the number of tourist visits to the operational cost of Sunari Hotel for the year 2016 amounted to 11.115%, it means up and down the operational costs at Sunari Hotel which is influenced 11.115% the number of tourist visits and the remaining 88.885% influenced by other factors.